Efektivitas Media Augmented Reality dalam Pembelajaran Struktur Atom di Sekolah Menengah - Damar Saputra; Sekar Melati Indah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to examine the effectiveness of Augmented Reality (AR) media in improving students' understanding of atomic structure. The background of this study is based on the importance of innovation in chemistry learning to improve students' engagement and understanding of concepts. The method used is an experiment with a pretest-posttest design, where students are divided into control and experimental groups. The results showed that the use of AR significantly improved students' understanding compared to conventional methods. These findings indicate that AR technology can be an effective tool in chemistry education to strengthen abstract concepts. The implications of this study indicate the need for technology integration in the learning process to improve the quality of science education.